FAKTOR – FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Suprapto, Visyka; Nugroho, Vidyarto (Jurnal Paradigma Akuntansi, 2025)
This research was conducted to gain empirical evidence about the effect of liquidity (CR), leverage (DER), total asset turnover (TATO), working capital turnover (WCT) and company size (SIZE) on the profitability of property and real estate companies listed on the IDX in 2019-2021. In this study, the purposive sampling method was used to obtain a valid sample of 96 data from 42 companies after outlier was conducted. This study uses multiple linear regression method to test the hypothesis and data is processed using SPSS version 26. The results of this research shows that leverage possess a negative and significant effect on profitability, while total asset turnover possess a positive and significant effect on profitability. On the other hand, liquidity, working capital turnover and company size do not have a significant effect on profitability. This research’s implication is that leverage needs to be reduced while total asset turnover needs to be increased to increase a company’s profitability.